MODELING OF THE HEAT PUMP STATION ADJUSTABLE LOOP OF AN INTERMEDIATE HEAT-TRANSFER AGENT (Part I) - Sit B. (Problems of the Regional Energetics)
There are examined equations of dynamics and statics of an adjustable intermediate loop of heat pump carbon dioxide station in this paper. Heat pump station is a part of the combined heat supply system. Control of transferred thermal capacity from the source of low potential heat source is realized by means of changing the speed of circulation of a liquid in the loop and changing the area of a heat-transmitting surface, both in the evaporator, and in the intermediate heat exchanger depending on the operating parameter, for example, external air temperature and wind speed.